VINAY AND DARBELNET’S TRANSLATING PROCEDURES USED IN TRANSLATING: ‘THE VILLAGE LEADER’ CHILDREN’S SHORT STORY BY ALYSSON CURRO - NOFATHANA SUPATRA; TIARA PANGESTUTI; SELI RAHMAWATI; NITA LESTARI (State University of Medan, 2024)
This study analyzed the translation procedures used in the translation of the children's short story